Strategies for Targeted Delivery of Exosomes to the Brain: Advantages and Challenges - Hojun Choi; Kyungsun Choi; Dae-Hwan Kim; Byung-Koo Oh; Hwayoung Yim; Soojin Jo; Chulhee Choi (Pharmaceutics, 2022)
Delivering therapeutics to the central nervous system (CNS) is difficult because of the blood–brain barrier (BBB). Therapeutic delivery across the tight junctions of the BBB can be achieved through various endogenous transportation mechanisms. Receptor-mediated transcytosis (RMT) is one of the most widely investigated and used methods. Drugs can hijack RMT by expressing specific ligands that bind to receptors mediating transcytosis, such as the transferrin receptor (TfR), low-density lipoprotein receptor (LDLR), and insulin receptor (INSR). Cell-penetrating peptides and viral components originating from neurotropic viruses can also be utilized for the efficient BBB crossing of therapeutics. Exosomes, or small extracellular vesicles, have gained attention as natural nanoparticles for treating CNS diseases, owing to their potential for natural BBB crossing and broad surface engineering capability. RMT-mediated transport of exosomes expressing ligands such as LDLR-targeting apolipoprotein B has shown promising results. Although surface-modified exosomes possessing brain targetability have shown enhanced CNS delivery in preclinical studies, the successful development of clinically approved exosome therapeutics for CNS diseases requires the establishment of quantitative and qualitative methods for monitoring exosomal delivery to the brain parenchyma in vivo as well as elucidation of the mechanisms underlying the BBB crossing of surface-modified exosomes.